CORRELATION BETWEEN HCV RNA VIRAL LOAD AND HOMA-IR IN CHRONIC HEPATITIS C PATIENTS - Nadhya Allia; Poernomo Boedi Setiawan; Soebagijo Adi Soelistijo (Universitas Airlangga, 2021)
Background: Insulin resistance (IR) is one of the extrahepatic complications of hepatitis C virus (HCV) infection that needs to be recognized early. HOMA-IR is an effective way to measure insulin resistancy. Core proteins, NS-3, and NS-5 are the main components of HCV RNA proteins which are involved in the incidence of IR. Seeing this, a hypothesis was developed that the level of HCV RNA viral load was related to the HOMA-IR. This study was designed to identify the correlation between HCV RNA viral load with HOMA-IR in chronic hepatitis C patients.Method: We conducted a cross-sectional approach from the medical record of chronic hepatitis C patients at the outpatient clinic dr. Soetomo Hospital, Surabaya. A total of 30 patients aged >19 years old with complete medical records were included. Clinical and laboratory (including HCV RNA viral load level and HOMA-IR) data were obtained from the availability of medical records.Result: A total of 30 chronic hepatitis C patients, 17 (56.7%) were women and 13 (43.3%) were men, with mean age was 50.90 ± 7.17 years. The median of HCV RNA viral load level was 3,14 x106 IU/ml and the median of HOMA-IR was 4.50. The result of the Spearman correlation test showed a moderate positive association between HCV RNA viral load and HOMA-IR (r=0.537 ; p=0.002).Conclusion: A positive moderate correlation was obtained between HCV RNA viral load with HOMA-IR in chronic hepatitis C patients.